2016
DOI: 10.1259/bjr.20140724
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective potential of carnitine against glycerol and contrast-induced kidney injury in rats through modulation of oxidative stress, proinflammatory cytokines, and apoptosis

Abstract: Depending on the underlying kidney pathologies, the incidence of CM-induced nephropathy (CIN) increases. Therefore, this is the best model to represent clinically observed CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…Decreased SOD activity and GSH levels have previously been reported in CIN, and different treatment strategies have ameliorated oxidative stress. 23 , 26 In accordance with the results of our study, Saritemur et al. showed decreased SOD activity and GSH levels in GLY-aggravated CIN, and treatment with infliximab increased SOD activity and GSH levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Decreased SOD activity and GSH levels have previously been reported in CIN, and different treatment strategies have ameliorated oxidative stress. 23 , 26 In accordance with the results of our study, Saritemur et al. showed decreased SOD activity and GSH levels in GLY-aggravated CIN, and treatment with infliximab increased SOD activity and GSH levels.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress, the perturbation of the balance between pro-oxidants and antioxidants, may underline the pathology of CIN. 23 , 26 EGCG has antioxidant activity, which is attributed to the galloyl group at the 3 position and the o-trihydroxyl group in the B ring in its structure, and it protects cells from damage by reactive oxygen species (ROS). Thus, EGCG may have an antioxidant effect on oxidative stress-induced impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies demonstrated the renoprotective effect by attenuating serum Cr and renal histological damage through their antioxidant activities (Table 4). Both inflammatory process and apoptosis were decreased following antioxidant treatments [35][36][37][38][42][43][44]. Active component of herbs; such as astragaloside, [45] curcumin, [46] grape seed proanthocyanidin, [47] lycopene, [48] magnolin (major active ingredient of herb Magnolia fargesii), [49] Phyllanthus emblica extract, [50] salidroside, [40] sesame oil, [51] and silymarin, [52] were investigated in CIN in rats (Table 4).…”
Section: Antioxidants As Interventions To Reduce Cinmentioning
confidence: 99%
“…L-carnitine is a naturally occurring amino acid derivative synthesized in the liver and kidney, it acts as a carrier for fatty acids acrossing the inner mitochondrial membrane, which is necessary for subsequent β-oxidation and ATP production [9]. The compound has been considered as a specific inhibitor of mitochondrial reactive oxygen species (ROS) [10], and the beneficial effects of which to protect kidney cells against oxidative stress, lipid peroxidation, proinflammatory cytokines, and apoptosis during acute and chronic kidney injury have been documented [11][12][13]. These pathogenetic factors have also been reported to play pivotal part in renal stone formation [14].…”
Section: Introductionmentioning
confidence: 99%